Chiral enhancement via surface-confined supramolecular self-assembly at the electrified liquid/solid interface. (10th August 2021) - Stoian, Ioan-Adrian; Iacob, Bogdan-Cezar; Ramalho, João P. Prates; Marian, Iuliu O.; Bodoki, Ede; Oprean, Radu
Abstract: A new simple and convenient strategy for boosting the enantioselectivity of cyclodextrins (CDs) as highly available homochiral macrocyclic hosts using the co-assembly of physisorbed propranolol (PRNL) enantiomers on gold nanoparticles (AuNPs) and different CDs was reported, exploiting the gainful effects of surface-confined supramolecular associations. All the experiments were conducted both in bulk enantiomer solution (unrestricted, homogenous system) and on the antipodes physisorbed at the gold-liquid interface (surface confined, heterogenous system), employing various electroanalytical techniques (differential pulse voltammetry, cyclic voltammetry and electrochemical impedance spectroscopy), isothermal titration calorimetry and computational modeling. In the unrestricted system, where the freedom of movement of PRNL molecules is not hampered, unassailable enantioselectivity may not be allocated to either of the tested CDs. However, by limiting the degrees of freedom of PRNL antipodes upon their adsorption to a non-chiral surface of electrochemically-generated AuNPs, a particular amplification of the conformational differences between the resulting supramolecular complexes with native CDs may arise. Molecular dynamics simulations of the supramolecular interactions on both homogenous and heterogenous system revealed important differences compared to the previously reported quantum chemical calculations performed in vacuo . Besides the advances of fundamental knowledge, this proof-of-concept data may offer an alternative strategy for the fast chiral probing of various analytes by interfacial supramolecular electrochemistry.